1997
DOI: 10.1089/aid.1997.13.63
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Nature of Noncytolytic CD8+T Cell-Mediated Suppression of HIV Replication: β-Chemokine-Dependent and -Independent Effects

Abstract: Chemokines were originally characterized by their ability to direct migration and induce activation of selected leukocyte populations. The beta-chemokines MIP-1 alpha, MIP-beta, and RANTES have been implicated in the suppression of viral replication by CD8+ T cells from HIV-infected individuals. The present study was undertaken to evaluate the effect of beta-chemokines on HIV replication in cocultures of dendritic cells (DCs) and CD4+ T cells, and an in vitro model of the lymphoid microenvironment. In the acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 24 publications
5
30
1
Order By: Relevance
“…Moreover, spontaneous chemokine production by the peripheral blood cells was also found to be quite variable. Similar findings on varying levels of chemokine production by T cells from HIV-infected or uninfected individuals have been reported by others (36,44).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, spontaneous chemokine production by the peripheral blood cells was also found to be quite variable. Similar findings on varying levels of chemokine production by T cells from HIV-infected or uninfected individuals have been reported by others (36,44).…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, the effector CD8 þ T cell subset, being higher in HIV ¹ Ethiopians than in HIV ¹ Dutch, decreased in Ethiopian HIV þ and AIDS subjects. This could result in less production of CCR-5 ligands (MIP-1a, MIP-1b, RANTES) and thus the potential inhibitory effect on HIV-1 cell entry would be decreased [41].…”
Section: Discussionmentioning
confidence: 99%
“…The most notable of these molecules are the natural ligands for the CCR5 coreceptors, the -chemokines RANTES, MIP-1 and MIP-1 , which do in fact inhibit viral replication by blocking viral entry. Since their discovery, however, several groups have shown that these soluble anti-viral factors cannot adequately explain the viral suppressive activity of CD8 + T cells [34,35]. Here we report that the anti-viral suppression occurs during transcriptional initiation of the HIV viral life cycle (using X4-tropic virus) and this will further ongoing studies into the precise molecules involved in suppressing viral transcriptional initiation.…”
Section: Discussionmentioning
confidence: 57%